Functional and clinical relevance of novel and known PCSK1 variants for childhood obesity and glucose metabolism - Dennis Löffler; Susanne Behrendt; John W.M. Creemers; Jürgen Klammt; Gabriela Aust; Juraj Stanik; Wieland Kiess; Peter Kovacs; Antje Körner (Elsevier, 2017)
Objective: Variants in Proprotein Convertase Subtilisin/Kexin Type 1 (PCSK1) may be causative for obesity as suggested by monogenic cases and association studies. Here we assessed the functional relevance in experimental studies and the clinical relevance through detailed metabolic phenotyping of newly identified and known PCSK1 variants in children. Results: In 52 obese children selected for elevated proinsulin levels and/or impaired glucose tolerance, we found eight known variants and two novel heterozygous variants (c.1095 + 1G > A and p.S24C) by sequencing the PCSK1 gene. Patients with the new variants presented with extreme obesity, impaired glucose tolerance, and PCOS. Functionally, c.1095 + 1G > A caused skipping of exon8 translation and a complete loss of enzymatic activity. The protein was retained within the endoplasmic reticulum (ER) causing ER stress. The p.S24C variant had no functional effect on protein size, cell trafficking, or enzymatic activity. The known variants rs6230, rs35753085, and rs725522 in the 5' end did not affect PCSK1 promoter activity.In clinical association studies in 1673 lean and obese children, we confirmed associations of rs6232 and rs6234 with BMI-SDS and of rs725522 with glucose stimulated insulin secretion and Matsuda index. We did not find the new variants in any other subjects. Conclusions: We identified and functionally characterized two rare novel PCSK1 variants of which c.1095 + 1G > A caused complete loss of protein function. In addition to confirming rs6232 and rs6234 in PCSK1 as polygenic risk variants for childhood obesity, we describe an association of rs725522 with insulin metabolism. Our results support the contribution of PCSK1 variants to obesity predisposition in children. Keywords: PCSK1, PC1/3, Obesity, Children, Prohormone convertase 1/3